Advanced Optimization Algorithm to Guarantee (N-1)-Security in Curative Congestion Management - Mehlem, Jonas; Gerdon, Christian; Moser, Albert (2023 International Conference on Future Energy Solutions (FES), 2023)
The introduction of nonlinear power flow controlling remedial actions and curative congestion management (CCM) increases the complexity of congestion management. State of the Art linearization approaches in the optimization of CCM can lead to violations of (n-1)-security not identified by algorithms based on linearization. This paper investigates the impact of exact outage simulations based on AC load flow equations and outage approximations based on linearization on the violation of (n-1)-security and computational effort in the optimization of CCM. Exemplary results show that exact outage simulations based on AC load flow calculation guarantee (n-1)-security at the cost of extreme computational effort. Outage approximations based on linearization can greatly reduce the computational effort, but can lead to violations of (n-1)-security by up to 7 %. Therefore, this paper introduces an advanced centralized algorithm combining linearized outage and exact outage calculations. The results show that the advanced centralized algorithm ensures (n-1)-security while increasing the computational effort in comparison to outage approximations by only a factor of between 39 % and 65 %.